Análisis semiótico del reinado de micaela lema en el imaginario social de Riobamba, durante el periodo abril 2017 - abril 2018 - Cynthia Lizbeth, Estrada Loroña (2019)
Data Mining is the process of exploring and analyzing large amounts of data to find patterns, trends and significant relationships (knowledge), through the application of algorithms and techniques that help to obtain relevant information. One of these is the K Nearest Neighbor (KNN) classification algorithm, which classifies new instances as the majority class among the nearest k neighbors. For the development of the research, the methodology of Knowledge Discovery in Databases (KNN) was used, as it is an automatic process in which discovery and analysis are combined. The application of the KNN algorithm was made through Weka, an open-source tool based on Java, excellent in classification tasks. Through the investigation it was evidenced that in the database of the COAC “Riobamba” Ltda. , there is stored relevant information about clients and the management of the credit and savings accounts, in order to classify the most important data that contribute to the investigation in a way that does not affect the clients. As a result of the research, potential clients were predicted and classified according to the demographic, economic, and internal aspects of the COAC “Riobamba” Ltda. So as to support the institution in making decisions regarding future credit offers. It concludes that it is important to take advantage of the information handled in each institution and more if it is the financial sector because both parties benefit, the clients because they will have easy access to more credit options and the financial institutions because they will increase their portfolio of clients and provide a better service.